POTRET NELAYAN SUNGSANG KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Efrianto A (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2018)
Fishermen are a community group that is always identified with people who are backward and tend tobe poor. The cause of the poverty of fishing communities is the limited ability to increase their productioncapacity and not optimally utilize and maintain their potential. This paper aims to find out how thebreeding fishermen work, describing fishing gear and profit sharing patterns applicable in the fishingcommunities of Sungsang. The type of this research is qualitative descriptive research with informantand key informant, some Sungsang fishermen, Sungsang community leaders and Banyuasin II subdistrict.This research was conducted in Sungsang Subdistrict Banyuasin II Banyuasin with data collectingtechnique that is through interview, observation, documentation, and library research by using technicalanalysis of interactive model data. Viewed from the aspect of fishing gear used by breeder fishermensociety can be stratified on various classes. While the income of fishermen depends on the pattern ofwork and their ownership of fishing gear.